2020
DOI: 10.1002/jdd.12404
|View full text |Cite
|
Sign up to set email alerts
|

In an era of uncertainty: Impact of COVID‐19 on dental education

Abstract: Purpose/Objectives The coronavirus disease 2019 (COVID‐19) pandemic arguably represents the worst public health crisis of the 21st century. However, no empirical study currently exists in the literature that examines the impact of the COVID‐19 pandemic on dental education. This study evaluated the impact of COVID‐19 on dental education and dental students’ experience. Methods An anonymous online survey was administrated to professional dental students that focused on their experiences related to COVID‐19. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
271
4
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(300 citation statements)
references
References 17 publications
(19 reference statements)
19
271
4
6
Order By: Relevance
“…The other aspects that the students appreciated were the possibility to follow the lectures again (to better understand the concepts), the flexibility of their schedule (to manage their logistics) and the lack of associated problems (such as lack of light in the room, projector problems). A recent survey by Hung et al (2020) also showed how dental students share concerns about their clinical education and their future, in terms of employment and recompense, which can add more stress to an already high-pressure profession [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other aspects that the students appreciated were the possibility to follow the lectures again (to better understand the concepts), the flexibility of their schedule (to manage their logistics) and the lack of associated problems (such as lack of light in the room, projector problems). A recent survey by Hung et al (2020) also showed how dental students share concerns about their clinical education and their future, in terms of employment and recompense, which can add more stress to an already high-pressure profession [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainties, like those reflected in the participants' responses, are not entirely surprising given that they "permeate every aspect of clinical practice-from diagnosing and managing dental caries to predicting success for [a treatment]" [10] and occur as early as during undergraduate dental education [27,28]. The COVID-19 pandemic has produced other uncertainties, considering information has changed almost daily due to the rapid rate knowledge is obtained about this novel coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…4 While students in dental settings have expressed concern about the quality of online instruction, years of reviews suggest that quality expectations will be met by participating in IDM. 5 The course also provided availability of subject experts and engagement with these experts as well as peer learners, meeting Reddy's suggestions for visibility and ventilation of educational materials and concepts as ways to maintain resilience during this time. 10…”
Section: Importance Of High-quality Virtual Materials Particularly Dmentioning
confidence: 99%
“…4 Although virtual learning presented significant challenges to all educators, the abrupt shift to this modality also posed opportunities, including the development and dissemination of online materials relating to dental education and the chance for faculty to obtain additional experience and knowledge of these previously unconventional methods. 5 Self-directed educational offerings moderated by experienced faculty, as often exist in massive open online courses (MOOCs), were found to be particularly useful methods of conveying content while allowing for student self-assessment. 2 In addition, the disruption to on-site education allowed dentistry to consider better preparation for future interruptions to education.…”
Section: The Covid-19 Pandemic's Impact On Dental Educationmentioning
confidence: 99%
See 1 more Smart Citation